Analisis Efektivitas Sistem Informasi Penelusuran Perkara (SIPP) bagi Pengguna Layanan Pengadilan: Studi pada Informasi Jadwal Persidangan di Pengadilan Negeri Surabaya - Fajriyah Lutfiyatul Hikmah; Eva Hany Fanida; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Digital transformation in judicial institutions is aimed at improving transparency, efficiency, and legal certainty for the public. One of the main instruments in the digitization of the judiciary in Indonesia is the Case Tracking Information System (Sistem Informasi Penelusuran Perkara/SIPP), which functions as a means of case administration as well as a medium for public information disclosure. Although SIPP is considered to be running well from an administrative perspective, its effectiveness from the point of view of service users, particularly in providing information on court schedules, still shows limitations in its practical use. This study aims to analyze the effectiveness of SIPP in providing information and certainty regarding court schedules for service users at the Surabaya Class IA Special District Court. This study uses a qualitative approach with a descriptive research type. Data was obtained through in-depth interviews with service users and court officials, observation, and review of documents and system data. The analysis was conducted using the Socio-digital effectiveness framework, which focuses on three dimensions, namely user experience, citizen engagement, and public value, to examine the relationship between digital systems, user experience, and the social meaning of public judicial services. The analysis shows that the SIPP has been quite effective in providing access to court schedule information at the administrative level. This effectiveness is reflected in the openness of information access, which can be used by the public without special authentication. However, at the level of practical use, there are still limitations in terms of timeliness and consistency of information updates when there are delays or changes to the court schedule. This affects the user experience in planning attendance and shapes perceptions of the reliability of the digital information provided by the court.